Caffeine and migraine – friends or enemies? - Ciuba, Katarzyna; Borodziuk, Barbara; Borodziuk, Filip; Dąbrowska, Paulina; Żuber, Michał; Bochyński, Karol; Molenda, Katarzyna; Dacka, Michał; Giżewska, Kamila; Białogłowski, Konrad (Quality in Sport, 2024)
Severe headaches or migraines are a common neurological disorder that can significantly affect people’s daily lives and is serious problem for individuals and society. A migraine is intense headache lasting 4-72 hours, typically localized on one side of the head and accompanied by nausea, sensitivity to light (phonophobia), sound (photophobia), and smell (osmophobia). The pathophysiology of migraines is complex and involves neurovascular and biochemicals mechanisms. Understanding the mechanisms that trigger the transition from a headache-free state to the headache phase is important to understand the underlying causes of migraine attacks and developing effective treatment methods. Caffeine can have both positive and negative influence on individuals suffering from migraine. It is use as adjuvant component in migraine treatment, but it can also act as a trigger for migraines. The therapeutic mechanisms of caffeine in migraine headaches are multidirectional and include: vascular effects, modulation of NO production, adenosine antagonism, potential interactions with the gut-brain axis and inhibition of leukotrienes and prostaglandins’ synthesis. On the other hand, the onset of migraine attack may be related to caffeine consumption or withdrawal. The purpose of this study is to review and systematize the available data about relation caffeine use to migraine.